Kemiskinan dan Perkembangan Wilayah di Kabupaten Boyolali - Wahyuni Apri Astuti; Muhammad Musiyam (Forum Geografi, 2009)
This research is based on the facts: first that, Boyolali is one of the regions which implement intensively many kinds of program in solving the poverty which gets the finance from APBD, central government and international institutions, eventhough the proportion of the poor society increases significantly.The proportion of poor society increases 20,8% in 2002 becomes 38,26% in 2006. Second, seen from the regional development indicator, it is shown that between one region and the others has various levels of the varieties of development.The objectives of this research are: first, the understanding of the distribution and of the poverty level in this region. Second, the understanding of the relationship between distribution of poverty level and the regional development level. Third, the understanding of the factors which influence the regional development. The method used in this research is secondary data analysis. The analysis unit of this research is village. The data resources are taken from the report of the identification result of poor families and the primary data is taken from BAPPEDA Boyolali. The primary data is a number of poor families, the regional scope and the use of farmland, the long street to account the regional accessibilities and the number and the distribution of social and economical facility in each village. The result is presented on the map with the analysis unit of the village. The represented map are the distribution level of poverty per village. To determine the relationship between the level of poverty and regional development uses the technique of qualitative and quantitative analysis. The qualitative analysis technique used is the analysis of the map of poverty distribution, analysis map of regional development and harmonious relationship between the level of regional development and poverty. The quantitative analysis technique used is the analysis of correlation statistic product moment.The results of this research are: first, there is distribution variation of poverty level, there is relationship between distribution of poverty level and natural resources endowment.The region with lower resources endowment (up land region) have higher poverty level than the region with higher natural resources endowment (law land region) and conversel. Second, there is negative relationship between regional development level and poverty level.Third, the factors which influence the level of regional development are the economical and social facility of the region and accessibilities.